Sudden Natural Death: Infectious Diseases - Kanchan, T. (Encyclopedia of Forensic and Legal Medicine, 2016)
A large number of sudden and unexpected deaths are caused by infections. Bacterial and viral infections remain the most common causes of sudden death from infectious diseases. Sudden deaths resulting from infectious causes involving the cardiovascular system are commonly reported due to myocarditis and infective endocarditis while sudden deaths involving the respiratory system are mostly due to pneumonia and tuberculosis. Detailed medicolegal investigation is warranted in sudden deaths due to infectious diseases involving a thorough autopsy and histopathological evaluation along with the use of microbiology and molecular diagnostic methods.